Analysis of Disturbing Influence of Traffic Load on Soil Body - Janat Musayev; Algazy Zhauyt (Advances in Materials Science and Engineering)
Stress waves propagate in soil in case of earthquake and man-made effects (traffic flow, buried explosions, shield-driven pipes and tunnels, etc.). The wave point-sources are those located at the distances equal to more than two waves lengths, which significantly simplifies solving of a problem of these waves’ strength evaluation. Distribution of stress and displacement by the stress waves propagation in elastic medium is a complex pattern. The stress distribution in propagating waves depends on the type and form of source, conditions of the source contact with medium, and properties of mediums in the vicinity of the source. The point-sources and their combinations are selected in such a way to model an influence of machines and processes on soil body in case of shield-driven pipes (tunnels).